2016
DOI: 10.18632/oncotarget.10417
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome-wide characterization of the endogenous miR-34A-p53 tumor suppressor network

Abstract: microRNA-34A is a critical component of the p53 network and expression of miR- 34A is down-regulated by promoter hypermethylation or focal deletions in numerous human cancers. Although miR-34A deregulation may be an important driver in cancer, the endogenous role of this microRNA in cellular homeostasis is not well characterized. To address this knowledge gap, we aimed to determine the transcriptional landscape of the miR-34A-p53 axis in non-transformed cells. Using primary skin-derived fibroblast cell lines f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Previous studies have demonstrated that miR-34a is a direct downstream target of p53, which is a tumor suppressor whose transcriptional targets regulate cell cycle, cell senescence, DNA repair, apoptosis and other biological behaviors [34, 35]. The p53-miR-34a network plays a crucial role in tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that miR-34a is a direct downstream target of p53, which is a tumor suppressor whose transcriptional targets regulate cell cycle, cell senescence, DNA repair, apoptosis and other biological behaviors [34, 35]. The p53-miR-34a network plays a crucial role in tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the p21 and BAX, p53 also is reported to activate the transcription of miR-34a, a potent tumor-suppressive miR, which gains much attention in recent cancer researches [20, 31]. This triggers our interest to investigate the effect of JP-1 on miR-34a transcription.…”
Section: Resultsmentioning
confidence: 99%
“…MiR-34a is the first identified and well-studied miR in the p53 regulatory network [20, 31]. Owing to its established role in cancer, synthetic miR-34a mimics are currently in Phase I clinical trials for lung and a variety of types of cancers (NCT01829971) [31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A component of TP53 tumor suppressor network, mir-34a represents another tumor suppressor gene that regulates cell proliferation by targeting cyclin D1 (CCDC1), cyclin-dependent kinase 4 (CDK4) and cyclin-dependent kinase 6 (CDK6) proteins or Wnt/β-catenin signaling pathway in laryngeal [50], breast [51] colon and cervical cancers [52].…”
Section: Mirnas Can Function As Oncogenes or Tumor Suppressor Genesmentioning
confidence: 99%